EFEKTIFITAS PENGGUNAAN MEDIA LCD DALAM LITURGI IBADAH MINGGU DI GEREJA - Saetban, Antonius; Suabuana, Cik (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
The use of Media of worship ceremony such as LCD projector should be fundamentally able to build a good relationship between the church and God through every element of the liturgy in worship service. This instrument of worship is now being popular in Christian churches which are mostly located in the big cities. Although its main function is to help the people to follow the liturgy during ceremony, this usage must be relied on the effectiveness factor; whether it helps the process of ceremony to close the Christians to God or not. This research aims to know more in depth the extent to which the effectiveness of the use of media in liturgical worship service Sunday at Peniel Church Oebobo Kupang City-East. While the specific goal is to determine the level of understanding regarding to the use of Media LCD congregation in the liturgy during the weekly services of church Pniel Oebobo. This research used descriptive with qualitative approach. Whereas, the techniques for collecting data were questionnaire and interviews in which researchers presented descriptive analysis of data and describe later discussions to draw conclusions and suggestions